Aortic valve neocuspidalization in paediatric patients with isolated aortic valve disease: early experience. (21st November 2020) - Polito, Angelo; Albanese, Sonia B; Cetrano, Enrico; Cicenia, Marianna; Rinelli, Gabriele; Carotti, Adriano
Abstract: OBJECTIVES: There is growing interest in the aortic valve (AV) neocuspidalization technique for the treatment of aortic valve disease (AVD). We report our medium-term results with this procedure performed in a paediatric patient population. METHODS: Between July 2016 and May 2020, 22 patients with both congenital and acquired isolated AVD were treated with neocuspidalization. The primary outcome was progression of the preoperatively assessed AVD in the immediate postoperative course and at follow-up. Secondary outcome was freedom from reintervention by material used. Potential predictors of failure were analysed in relation to the primary outcome. RESULTS: The median age at operation was 13.9 (interquartile range, 9.8–16.2) years, and the prevailing AV defect was stenosis in 10 cases (45%) and incompetence in 12 (55%). Pre-treated autologous pericardium was used in 13 patients whereas bovine pericardium in 9. Effective treatment of AV stenosis or regurgitation was achieved and remained stable over a median follow-up of 11.3 (4.7–21) months. Three patients required AV replacement at 4.9, 3.5 and 33 months. At follow-up, an upward trend of both median indexed vena contracta jet widths and aortic peak and mean gradients were recorded, the latter associated with a failure to grow the aortic annulus. Predictor of such outcome turned out to be the use of bovine pericardium. A significant inverse linear correlation between AV peak gradient at follow-up and preoperative aortic annular size ( P  = 0.008) was also demonstrated. CONCLUSIONS: The Ozaki procedure is safe and effective in paediatric patients with AV disease. The use of heterologous pericardium should probably be minimized. Moreover, preoperative small aortic annuli should probably be promptly treated by means of an associated ring enlargement procedure.